Strategic option for SMEs in global business environment: A Malaysian perspective - Hashim, Mohd Khairuddin; Mad, Che Ani (Universiti Utara Malaysia Press, 2005)
The rapidly emerging global business has already raised a multitude of problems for small and medium-sized enterprises (SMEs). Small and medium-sized enterprises are facing increasing competition both nationally and internationally, increasing internationalization of markets, and new global competitors. Small and medium-sized enterprises,therefore, need to determine the strategic options that can help them overcome these changes.To address this issue, this paper identifies and discusses seven viable strategic options for SMEs from the Malaysian perspective.